ANALISIS PENGARUH EVA DAN ROA TERHADAP RETURN SAHAM PADA INDUSTRI KONSUMSI DI BURSA EFEK INDONESIA - Pungky Hapsari (Universitas PGRI Madiun, 2013)
This study aimed to determine the effect of Economic Value Added (EVA) and Return On Assets (ROA) of stock returns on consumption listed companies on the Stock Exchange during the years 2006-2008. Purposive sampling technique with sampling and eventually acquired 29 companies that meet the criteria to be used as the study sample. The analysis model used in this study is the linear regression that aims to discover whether there is any empirical evidence of the influence of Economic Value Added (EVA) and Return On Assets (ROA) to stock return. The analysis showed that the simultaneous EVA and ROA significantly α = 5% of the stock return, but partially EVA no significant effect on stock returns. While ROA partially significant effect on stock returns. For regression coefficients show negative EVA while ROA is positive.